2019
DOI: 10.4018/ijbir.2019010103
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Capability Readiness Towards Business Intelligence Implementation

Abstract: Business intelligence (BI) has widely been recognized due to its growing applications in improving the decision-making support. The growing trend of BI applications necessitates a study on organizational capability readiness which offers significant effects in BI implementations. However, a limited number of studies focused on issues related to organizational capability readiness for BI implementations. Therefore, this study aims to analyze and explore an integrated view of literature in relation to organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In order to frame the following conventions within the context of continuous improvement, they adopt recent, relevant, and accepted interpretations of "Business Readiness" [47][48][49]. This refers to a process for managing change within an organisation.…”
Section: Conventionmentioning
confidence: 99%
“…In order to frame the following conventions within the context of continuous improvement, they adopt recent, relevant, and accepted interpretations of "Business Readiness" [47][48][49]. This refers to a process for managing change within an organisation.…”
Section: Conventionmentioning
confidence: 99%
“…The combination of better results and efficiency is a consequence of high-quality decision-making, which is made easier by better Information Management Capability (Shamim, Zeng, Shariq, & Khan, 2018). Studies have shown that IMC has a positive impact on companies' performance (Carmichael, Palacios-Marques, & Gil-Pechuan, 2011;Mithas, Ramasubbu, & Sambamurthy, 2011); this impact can be direct (Carmichael et al, 2011) or mediated by other organizational skills (Ali & Khan, 2019;Levallet & Chan, 2018;Mithas et al, 2011). Information Management Capability can be understood as a set of company skills that support information infrastructure, architecture, and access, as well as its distribution, which enables organizational adjustments in response to changes imposed by internal and external environments.…”
Section: Introductionmentioning
confidence: 99%
“…Information Management Capability can be understood as a set of company skills that support information infrastructure, architecture, and access, as well as its distribution, which enables organizational adjustments in response to changes imposed by internal and external environments. This construct must also be taken into consideration within the Big Data and Analytics contexts (Ali & Khan, 2019; because it would indicate the relationship between these skills and the company's strategic performance (Mikalef, Pappas, Krogstie, & Giannakos, 2018). "The strategic IS research field is a rich source of evidence that can be used to illustrate resource complementarity issues" (Wade & Hulland, 2004, p. 123).…”
Section: Introductionmentioning
confidence: 99%